Genetically modified pigs with α1,3-galactosyltransferase knockout and beyond: a comprehensive review of xenotransplantation strategies - Stelcer, Ewelina; Wozniak, Anna; Magner, Dorota; Zeyland, Joanna (Frontiers in Immunology, 2025)
Xenotransplantation holds promise to eliminate the shortage of organs intended for humans in need. Pigs constitute the most suitable organ xenograft donor due to the fact that their organ anatomy physiological metabolism and immune system resemble those of humans. However, swine organs rapidly cause hyperacute rejection (HAR) and acute humoral xenograft rejection (AHXR) after transplantation. HAR and AHXR are caused by the presence of xenoreactive natural immunoglobulins directed toward a galactose alpha1-3-galactose (alpha-Gal) epitope on porcine vascular endothelium. In order to suppress both types of rejection, pigs with alpha1,3-galactosyltransferase gene knockout (GT-KO) and other genetic modifications (like simultaneous expression of the human complementary regulatory proteins) are intensively investigated. This review highlights the usefulness of GT-KO pig – derived organs such as kidney, heart, corneal, and lung in xenotransplantation. To obtain transgenic pigs researchers can use several techniques based on pronuclear and cytoplasmic microinjection, somatic cell nuclear transfer (SCNT), viral transduction of DNA and DNA transposable element -based technology, site specific nucleases and modifications of the CRISPR/Cas bacterial immune system. Some additional strategies like targeted immunosuppression or tolerance induction of B and T cells will be essential for sustained survival of xenografts. Although xenotransplantation with the use of pigs is a very rapidly evolving field, more research is needed to create perfectly compatible with the human immune system organs.